I-Mutawwif : mobile language traveller guide in Arabic for mutawwif (umrah tour guide) via smart phones - Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Zubir, Muhamad Azhar; Ismail, Taufik (2017)
This paper is focusing on the design and development of a mobile language guide application in Arabic language for Mutawwif (Umrah Tour Guide) through smart phones in Android supported platform via ADDIE model. The D&D process was done based needs analysis process among 100 Mutawwif at a national conference of Mutawwif organized at USIM, Nilai, Negeri Sembilan, Malaysia on 18 October 2016, whereby the evaluation on user testing session was conducted among 50 purposively selected respondents from 30 mutawwif at Andalusia Travel and Tours company and 20 learners at Baitul Mal Professional Institute, MAIWP under the specialization of Diploma in Hajj and Umrah Management from 26 March until 20 April 2017.